Love for Levon [videorecording (DVD)] : a benefit to save the barn - McAnally, Conor; Campbell, Larry, 1955-; Was, Don; Haynes, Warren; Jaffee, Rami, 1969-; Allman, Gregg, 1947-2017; Kaukonen, Jorma; Mitterhoff, Barry; Guip, Justin; Isaacs, Byron; Jaimoe; Pelton, Shawn; et al. (StarVista Entertainment : Time Life, 2013)
Benefit concert in honor of Levon Helm.